Systemic Functional Analysis of NATO’s Linguistic Strategies to Debunk Russian Information Warfare - Muhammad Andrean Syahsurya; Fariq Shiddiq Tasaufy (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
Information warfare has become a vital area in modern geopolitical battles because language functions as both a combat tool and a defensive mechanism. The research investigates NATO's development of epistemic authority in counter-disinformation discourse through Systemic Functional Linguistics (SFL) analysis. The study analyzes NATO's "De-bunking Russian disinformation on NATO" webpage to identify linguistic methods that affect thematic structure and ideational, interpersonal, and textual metafunctions. The thematic analysis showed NATO stands as a central theme throughout multiple clauses, which confirms its essential role in the text. The research used strategic deployment of Marked Themes to create historical frameworks through temporal markers and to perform acknowledge-then-refute moves through concessive markers and to emphasize evaluation through manner markers. The research findings demonstrate how SFL applies to counter-disinformation discourse while showing thematic analysis effectiveness and revealing how integrated metafunctional analysis reveals collaborative meaning creation processes. The research study shows how NATO uses four main strategies, which include empirical evidence, confident statements, systematic counterarguments, and strategic thematic emphasis. The thematic progression followed three patterns, which included maintaining constant theme focus and linear argument development, and derived progression for maintaining textual coherence. The research demonstrates that grammatical selection methods establish epistemic authority through consistent patterns that appear throughout different metafunctional layers. The research establishes a complete framework that enables researchers to conduct future counter-disinformation studies in various institutional settings.